A case of secondary localized pericardial cyst hydatic disease and determination of cyst hydatic scoleces and hooks with various stains - Rahman, Ali; Yücel, Ahmet; Yilmaz, Mustafa (My University, 2008)
A sixty-six year-old male patient with the complaint of palpitation presented at the out-patient clinic of the thorax diseases department. The patient underwent open heart surgery (cystectomy and capitonage) for the cystic hydatidosis which was located on the front wall of the right atrium and extended to the atrioventricular cleavage. Albendazol treatment (2 x 400 mg/3 months) was given postoperatively. The complaints of the patient reoccurred 2 years later, and a cystic formation measuring 45 cm by 2.5 cm was observed by transoesaphageal echocardiography. During pathological examination, the specimen obtained from the patient during surgery was diagnosed as cystic hydatic disease, and a final diagnosis was made after the observation of scoleces and hooks in the microbiology and parasitology laboratory. Cyst ingredients were centrifuged, and then stained with carbol-fuchsin, methylene blue, Giemsa, and Ziehl Nielsen methods in order to see scoleces and hooks of the parasite. The authors presented this case both because of the rare location and staining characteristics of the parasite with different staining methods.
Sekonder Yerleşimli Bir Perikardiyak Kist Hidatik Olgusu ve Kist Hidatik Skoleks ve Cengellerinin Bazi Boya Solüsyonlari ile Boyanmasi.
Keywords: Aged; Albendazole; Animals; Anthelmintics; Echinococcosis; Echinococcus granulosus; Heart Atria; Humans; Male; Mediastinal Cyst; Staining and Labeling; albendazole; anthelmintic agent; aged; animal; article; case report; echinococcosis; Echinococcus granulosus; echography; heart atrium; human; isolation and purification; male; mediastinum cyst; methodology; parasitology; staining